(untitled) (Academic Journal of Internal Affairs, 2023)
Aim: The review draws attention to a publication that initiates changes in the practice of law enforcement, and calls for the help of p olice science. Complementary policing is the product of a partnership between security authorities and a law-abiding society. The book by László Christián gives details of this process. Methodology: This monograph makes its recommendations based on the reality of everyday life, using factual analysis typical of social science research. Research on modern policing was limited to public law dogmatics for a long time. However, when the public authority’s surveillance of security is complemented by individual and collective forms of social care and the market services of property protection, the interpretation of the law is insufficient for exploration, and it is worthwhile to turn to the methodologies offered by sociology. Findings: The actors of the complementary model are law enforcement authorities, municipalities, individual and community self-defence and the security market. The best conditions for this cooperation can be created in a democratic state governed by the rule of law. Value: The exploration of the regularities of cooperation between the sectors responsible for law and order is a scientific achievement that can contribute to the lawful and efficient functioning of law enforcement administration, the protection of public security and the harmony of order, security and freedom.